Light means power: harnessing light spectrum and UV-B to enhance photosynthesis and rutin levels in microtomato plants - Lima, Iury Henrique Almeida; Rodrigues, Arthur Almeida; Resende, Erika Crispim; da Silva, Fábia Barbosa; Farnese, Fernanda dos Santos; Silva, Lucas de Jesus; Rosa, Márcio; Reis, Mateus Neri Oliveira; Bessa, Layara Alexandre; de Oliveira, Thales Caetano; Januário, Ana Helena; Silva, Fabiano Guimarães (Frontiers in Plant Science, 2023)
Urban vertical agriculture with lighting system can be an alternative green infrastructure to increase local food production irrespective of environmental and soil conditions. In this system, light quality control can improve the plant physiological performance, well as induce metabolic pathways that contribute to producing phenolic compounds important to human health. Therefore, this study aimed to evaluate the influence of RBW (red, blue and white) and monochromatic (red and blue; R and B, respectively) light associated or not with UV-B on photosynthetic performance and phenolic compound production in microtomato fruits cultivated via vertical agriculture. The experimental design adopted was completely randomized, with six replicates illuminated with 300 µmol·m−2·s−1 light intensities (RBW, RBW + UV, B, B + UV, R, and R + UV), 12 h photoperiod, and 3.7 W·m−2 UV-B irradiation for 1 h daily for the physiological evaluations. Twenty-six days after the installation, gas exchange, chlorophyll a fluorescence and nocturnal breathing were evaluated. Fruits in different ripening stages (green, orange, and red) were collected from microtomato plants grown under with different light qualities, to evaluate the physiological performance. The identification and quantification of the phenolic compound rutin was also performed to investigate their metabolic response. This study identified that plants grown under B + UV had high photosynthetic rates (A=11.57 µmol·m−2·s−1) and the fruits at all maturation stages from plants grown under B and B + UV had high rutin content. Meanwhile, the activation of suppressive mechanisms was necessary in plants grown under R because of the high nocturnal respiration and unregulated quantum yield of the non-photochemical dissipation of the photosystem II. These results highlight the importance of selecting light wavelength for vegetable cultivation to produce fruits with a high content of specialized metabolites that influence color, flavor, and health promotion, which is of special interest to farmers using sustainable cropping systems.